Poetry Reading: Activities of ordering and sequencing questions in Elementary School - Fuza, Ângela Francine; Menegassi, Renilson José (INTERFACES DA EDUCAÇÃO, 2025)
The objective of this study is to present and discuss the theoretical-methodological proposal of ordering and sequencing of poetry reading questions in Elementary School, in order to contribute to the studies on the teaching and learning of Portuguese, both in reading skills and in written textual production. The work is based on the concepts of reading, with emphasis on the studies of Applied Linguistics and the practice of ordering and sequencing reading, pointing out the relevance of this proposal as part of the student's development process, as a reader and a writer at school. In preparing the proposal, the following are considered: (I) the survey of the main ideas of the text; (II) the elaboration of a text from those ideas; (III) the creation of reading questions based on the listed ideas; (IV) the student-reader’s production of a text as a replica/counterword based on the answers given. From the elaboration of the proposal for ordering and sequencing the questions, the results indicate: (a) the identification of main ideas of the text; (b) the student's position on the theme of the text; (c) the production of text as a replica/counterword as a result of the whole process.